The Role of Officers from the Special Child Development Institution Class II Banda Aceh in Dealing with the Adjustment Problems of Juvenile Inmates - Jarnawi, Jarnawi; Indra, Saiful; Zain, Arifin; Wulandari, Putri; Maturidi, Maturidi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
Self-adjustment is difficult for correctional students (Andikpas) in the Special Development Institute for Children (LPKA). The life of Andikpas before entering LPKA is more directed towards freedom but in LPKA Andikpas are required to be able to follow the rules and must be able to adapt to their new environment. This study aims to determine the description of the problem of self-adjustment of Andikpas in LPKA Class II Banda Aceh and the role of LPKA Class II Banda Aceh Officers in overcoming the problem of self-adjustment of Andikpas. This research uses a qualitative method approach. The data collection techniques used are interviews, observation, and documentation techniques. The results of this study found that the problems felt and experienced by children in LPKA Banda Aceh are feelings of fear and anxiety, feelings of guilt, disappointment, and sadness because they are away from their families, difficulty accepting themselves, and lack of a sense of responsibility for themselves. So, to overcome these problems, LPKA officers provide services, guidance, supervision, and implementation of religious, educational, independence, and skills development programs for Andikpas at LPKA Class II Banda Aceh so that correctional students can better adjust to themselves and their community environment.